Complexidade e interatividade como produtos artísticos: a poética musical de Jacob Collier - Maciel, Caio Jose Rodrigues (2022)
This work investigates Jacob Collier's artistic production, seeking to understand to what extent the combination of complexity and interactivity characterize his work, and how the artist uses New Media as a tool for creative innovation. We start from the hypothesis that Collier's musical poetics, despite the degree of complexity involved in his artistic processes, results from a successful proposal of interactivity at different levels of complexity. The proposed debate is located in the field of studies of Audiotactile Music and Ubiquitous Music, and considers theoretical references on art and culture in the modern era, use of technology as a creative and interactivity tool, musical analysis, harmony, relationship between image and sound and audiovisual aesthetics.